Produção de chapas de partículas com resíduos de madeira Cordia goeldiana - Christoforo, Andre L.; Silva, Sergio A. M. da [UNESP]; Barbosa, Juliana C. [UNESP]; Ribeiro Filho, Sergio L. M.; Panzera, Tulio H.; Lahr, Francisco A. R. (Soc Brasil Engenharia Agricola, 2015)
The aim of this research consisted in the use of wastes from tropical wood (Cordia goeldiana) with low density and the polyurethane resin (mono and bicomponent) castor oil based in the manufacture of particleboards, generating subsidies as application in rural and civil construction, as well in the furniture industry. The particleboards were manufactured with 15% of polyurethane resin content (one part of pre-polymer and one part of polyol), compaction pressure of 4MPa, pressing temperature of 90 degrees C and press time of 7 minutes. The physical and mechanical properties investigated were density, moisture content, strength modulus in bending and internal bond, both obtained according to the recommendations of the Brazilian standard ABNT NBR 14810:2002. The mean values obtained for these properties were systematically superior to the Brazilian standard requirement. This point showed that it is possible the use of Cordia goeldiana wastes in the particleboard production. We confirmed the hypothesis of a significant linear relation between density and the internal bond of the panels, allowing the estimation of the internal bond of particleboards.

O objetivo deste trabalho consistiu no aproveitamento de resíduos de madeira tropical de baixa densidade (Cordia goeldiana) para confecção de chapas de partículas com resinas poliuretanas monocomponente e bicomponente derivadas de óleo de mamona, gerando subsídios como aplicação nas construções rurais e civis, assim como na indústria moveleira. As propriedades físicas e mecânicas investigadas foram: densidade; teor de umidade; módulo de resistência na flexão estática e adesão interna, ambas obtidas segundo os procedimentos de cálculo propostos pela norma Brasileira NBR 14810:2002. As chapas foram confeccionadas com 15% de resina (uma parte de poliol para uma parte de pré-polímero), 4MPa de pressão de compactação, temperatura de prensagem de 90oC e tempo de prensagem de 7 minutos. Os valores médios obtidos das propriedades físicas e mecânicas das chapas foram sistematicamente superiores aos requisitos da norma Brasileira, evidenciando a possibilidade do emprego dos resíduos da madeira de Cordia goeldiana na produção de painéis de partículas. Confirmou-se também a hipótese da significativa relação linear entre a densidade das chapas com a adesão interna, o que possibilita a estimativa da adesão interna para painéis de partículas de madeira.
Particleboards manufactured with Cordia goeldiana wood wastes
Keywords: Particleboards; Polyurethane resin; Tropical wood wastes; Painéis de partículas; Resina poliuretana; Resíduos de madeiras tropicais